Expansion of CD11b⁺Ly6G⁺Ly6Cint cells driven by medroxyprogesterone acetate in mice bearing breast tumors restrains NK cell effector functions - Spallanzani, Raúl Germán (2013)
The progesterone analog medroxyprogesterone acetate (MPA) is widely used as a hormone replacement therapy in postmenopausal women and as contraceptive. However, prolonged administration of MPA is associated with increased incidence of breast cancer through ill-defined mechanisms. Here, we explored whether exposure to MPA during mammary tumor growth affects myeloid-derived suppressor cells (MDSCs; CD11b⁺Gr-1⁺, mostly CD11b⁺Ly6G⁺Ly6Cint and CD11b⁺Ly6G⁻Ly6Chigh cells) and natural killer (NK) cells, potentially restraining tumor immunosurveillance. We used the highly metastatic 4T1 breast tumor (which does not express the classical progesterone receptor and expands MDSCs) to challenge BALB/c mice in the absence or in the presence of MPA. We observed that MPA promoted the accumulation of NK cells in spleens of tumor-bearing mice, but with reduced degranulation ability and in vivo cytotoxic activity. Simultaneously, MPA induced a preferential expansion of CD11b⁺Ly6G⁺Ly6Cint cells in spleen and bone marrow of 4T1 tumor-bearing mice. In vitro, MPA promoted nuclear mobilization of the glucocorticoid receptor (GR) in 4T1 cells and endowed these cells with the ability to promote a preferential differentiation of bone marrow cells into CD11b⁺Ly6G⁺Ly6Cint cells that displayed suppressive activity on NK cell degranulation. Sorted CD11b⁺Gr-1⁺ cells from MPA-treated tumor-bearing mice exhibited higher suppressive activity on NK cell degranulation than CD11b⁺Gr-1⁺ cells from vehicle-treated tumor-bearing mice. Thus, MPA, acting through the GR, endows tumor cells with an enhanced capacity to expand CD11b⁺Ly6G⁺Ly6Cint cells that subsequently display a stronger suppression of NK cell-mediated anti-tumor immunity. Our results describe an alternative mechanism by which MPA may affect immunosurveillance and have potential implication in breast cancer incidence.